APPLYING MATH REVIEW GAME METHOD IN ORDER TO INCREASE COGNITIVE LEARNING OUTCOMES AND STUDENTS INVOLVEMENT LEVEL IN MATHEMATIC LESSON - Di Ohanes Richi Christian Plenden; Gamaliel Septian Airlanda (Jurnal Basicedu, 2019)
This research purposed to increasing cognitive learning outcomes and involvement level of Mountainview Christian Elementary School fifth grade students with applying active learning and review game method. The research that be done is Classroom Action Research which had two cycle. Data in this research gotten from observation, questionnaire, and test then analyzed in percentage form. Learning outcomes result analyzed based on the minimum completeness criteria percentage whether individual or general. The result of the research show that the student learning outcomes result in general increased. In the first cycle the students that pass the minimum completeness criteria was 85% and increased in the second cycle become 100% , the learning outcomes average in the first cycle is 9.23 increased in the second cycle become 9.73. learning outcomes that increased also followed by the increasing of student involvement level about 15% from the first cycle which is 54% categorized as enough become 77% in the second cycle categorized as active. From this research result concluded that the applying of active learning with review game could increasing cognitive learning outcomes and involvement level of the students.